DAYA TARIK WISATA PADA DESTINASI WISATA AIR TERJUN ANAK SUNGAI KANDI KECAMATAN HULU KUANTAN KABUPATEN KUANTAN SINGINGI RIAU - Yudha, Teddy Wira; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study explores the tourist attractions of the Anak Sungai Kandi Waterfall in Hulu Kuantan District, Kuantan Singingi Regency, Riau Province. Using qualitative descriptive methods, this study identifies various factors that contribute to the destination's strengths, including its natural beauty, supporting facilities, and the active role of the community through the Tourism Awareness Group (Pokdarwis) in tourism management. The results indicate that the main attractions of this tourist attraction lie in its pristine natural conditions, the captivating waterfall, and the socio-cultural values of the local community. However, challenges such as limited infrastructure and suboptimal community participation hinder its further development. This study recommends improving infrastructure quality, strengthening tourism promotion, and empowering the community as strategic steps to support sustainable tourism development in the area. Keywords: Waterfall, Tourist Attraction, Pokdarwis